The Effect of Price Transparency on Young Travellers’ Choices: An Experimental Study of Resort Packages - Nazlan, Nadia Hanin (Information Management and Business Review, 2024)
Product bundling has gained significant traction in the hospitality industry, with an increasing number of businesses offering all-inclusive resort packages to attract consumers. With the increase in online travel purchases, both academics and industry professionals are increasingly interested in understanding the factors influencing consumer travel package choices. This study employs a 2 x 5 mixed-design experiment where participants evaluated both an all-inclusive and a non-inclusive resort, with variations in price presentation. Pricing was presented either transparently or non-transparently, and package savings were displayed in multiple formats. The results reveal a strong consumer preference for all-inclusive resort packages, regardless of the perceived value. Moreover, how pricing information is presented plays a crucial role in shaping consumer purchase decisions. These findings highlight the importance of price presentation strategies in the marketing of travel packages and offer valuable insights for both marketers and practitioners in the hospitality sector.